Robert Southey - Andrews, S. author. aut Link
XIX, 250 p.
Keywords: In Robert Southey , Andrews argues that Robert Southey's denunciation of global Catholicism is essential to understanding his life, works, and times. On this issue, Southey was absolutely consistent in all his work and the Poet Laureate's partisan rhetoric reveals much about the religious culture of this stormy period in England.